Volatile and non-volatile metabolite changes in 140-day stored vacuum packaged chilled beef and potential shelf life markers. (March 2020) - Frank, Damian; Hughes, Joanne; Piyasiri, Udayasika; Zhang, Yimin; Kaur, Mandeep; Li, Yutao; Mellor, Glen; Stark, Janet
Abstract: During storage of vacuum packaged chilled beef (VPCB), lactic acid bacteria become the dominant microflora, facilitating an extended shelf life. However, at some point, (bio)chemical and organoleptic changes render the meat unacceptable. In this investigation we evaluated volatile and non-volatile metabolite changes in VPCB after 84-, 98-, 120- and 140-days storage at − 1 °C. After 140-days storage, the sensory, volatile and non-volatile data did not indicate spoilage. Minimal changes in volatile signatures of collected weep and on raw and grilled steaks were measured. Changes in selected non–volatile components indicated increased proteolysis (free amino acids, carnosine) and changes in organic acids (lactic, succinic) and nucleotide metabolism. Rapid volatile profiling using proton transfer reaction mass spectrometry showed a clear progression of changes in selected compounds over the storage period. An increased concentration of ethanol and other compounds between 120 and 140 days, suggested that volatile changes may be a useful objective indicator of extended storage VPCB quality.